Lymphatic Filariasis: Progress Towards Elimination - Ranganath BG (Journal of Clinical and Biomedical Sciences)
Preventive chemotherapy (PC) is now a widely used strategy to treat populations at risk of helmin-thic diseases to prevent its transmission and to reduce morbidity among those affected by it. PC is now elim-ination/control strategies for lymphatic filariasis (LF), soil-transmitted helminthiasis (STH) namely, hook worm infestation, ascariasis and trichuriasis, onchocerciasis, schistosomiasis and also trachoma a bacterial infection. Mass drug administration (MDA) and morbidity management are the major public health measures required for elimination of LF. Annual progress on elimination interventions of LF is submitted by the endemic countries to the WHO. Notable progress and achievements have been made by few countries in LF elimination. Many countries are on a path towards LF elimination by 2020. Few countries are yet to initi-ate campaigns towards elimination. Countries claiming LF elimination are to be validated by the WHO and should meet the eligible requirements. Sustenance of the claim post-elimination assessed by transmission assessment surveillance (TAS) is a challenge. For those countries that are still in the earlier phase of elimi-nation campaign, alternative faster approaches to achieve it are an immediate need and a challenge to the programme strategists. Key words: Lymphatic filariasis (LF), elimination, transmission assessment surveillance (TAS), mass drug ad-ministration (MDA), preventive chemotherapy (PC), morbidity management and disability prevention (MMDP)